Nonlinear creep response of oriented polypropylene tapes. (December 2018) - Barkoula, Nektaria M; Alcock, Ben; van Erp, Tim B; Govaert, Leon E; Peijs, Ton
The creep response of a highly oriented polypropylene tape used for the manufacture of self-reinforced polypropylene or all-polypropylene composites was studied over a range of stresses and temperatures. Similar to oriented polyethylene, the creep compliance is linear viscoelastic at short loading times, whereas pronounced stress dependence is observed at longer loading times. A mathematical model is proposed, where the total deformation of the fibre is regarded as being composed of a stress-linear delayed elastic component and a nonlinear plastic flow contribution. Model predictions are in good agreement with the experimental data.